Pengaruh Media Kartu Kata Berbasis Video Animasi Terhadap Keterampilan Membaca Permulaan Pada Siswa Kelas 1 SD Negeri 12 Toboali - Sasi Mardita; Vika Martahayu; Nurjanah (Universitas Muhammadiyah Bangka Belitung, 2026)
This study was motivated by the low level of students’ beginning reading skills. The purpose of this study was to determine whether there is an effect of animated video-based word card media on the beginning reading skills of Grade I students at SD Negeri 12 Toboali. This research employed a quantitative approach with a pre-experimental method, using a one-group pretest-posttest design. The sample consisted of one class of 25 students selected through a saturated sampling technique. Students were given an oral test consisting of five questions as the data collection technique. Data were analyzed using the normality test (Shapiro-Wilk) and hypothesis testing (Paired Sample t-test). The results of the normality test showed that the pretest data had a significance value of 0.105, which is greater than 0.05, and the posttest data had a value of 0.133, which is also greater than 0.05, indicating that the data were normally distributed. The results of the paired sample t-test showed a significant difference between the pretest and posttest scores (0.000 < 0.05), with posttest scores significantly higher than pretest scores. Therefore, Ho was rejected and Ha was accepted. It means that using animated video-based word card media significantly affects the beginning reading skills of Grade I students at SD Negeri 12 Toboali.